PENGARUH ION Cu(II) DAN ION Ni(II) TERHADAP EFEKTIVITAS FOTOREDUKSI ION Cr(VI) TERKATALISIS TiO2 - , Eni Kartika Sari; , Prof. Dr. Endang Tri Wahyuni, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Influences of Cu(II) and Ni(II) ions with variation of concentration on the photoreduction of Cr(VI) ion photocatalyzed by TiO 2 have been studied. The photoreduction process was carried out by irradiating a mixture of Cr(VI) ion solution and TiO 2 photocatalyst powder in the presence and the absence of either Cu(II) or Ni(II) ion in a closed reactor equipped with UV lamp and under continous stirring. Conditions of the photoreduction were 50 mL of Cr(VI) ion 0,05 mmol/L with 30 mg of TiO2 for 24 hours of the reaction time with varied concentration of Cu(II) and Ni(II). The reduced Cr(VI) was calculated based on the difference between the initial and final concentration of Cr(VI). The remaining Cr(VI) was analyzed by using UV/Vis spectrophotometer. The results showed that the photoreduction of Cr(VI) reduced by the increasing of Cu(II) concentration due to competition in photoreduction and adsorption. Meanwhile the presence of Ni(II) ion did not influence the photoreduction of Cr(VI) ion but it reduced the adsorption. Irradiation in the presence of TiO 2 toward electroplating waste which containing Cr(VI), Cu(II) and Ni(II) ions reduced the concentration of the metals. The increasing of the reduction of metals due to the increasing of TiO2 mass until 30 mg for Cr(VI) ion and 15 mg for Cu(II) ion. With addition of photocatalyst mass lead to decrease the reduction. The crystallinity of TiO2 decreased after it is used as photocatalyst in photoreduction of Cr(VI) ion in the presence of Cu(II) or Ni(II) ions.